Comparative Bioavailability of Four Marketed Sparfloxacin Formulations in Healthy Human Volunteers - K. Ravindra Rao; J. Vijaya Ratna; T. Manikya Rao (E-Journal of Chemistry)
The objective of the study was to obtain the pharmacokinetic data of four marketed tablet formulations of sparfloxacin and compare the relative bioavailability of the formulations with standard formulation. A single dose 4×4 latin square design of the four marketed tablet formulations of sparfloxacin (200 mg) was carried out in four healthy male volunteers. Blood samples were collected at predetermined time intervals. The serum concentrations of the drug were determined by microbiological assay. The pharmacokinetic parameters were calculated from the plasma concentration of sparfloxacin versus time data. The AUC0-α of the sparfloxacin from products A, B, C and D was 23.33±3.90 μg h/mL, 19.72±2.47 μg h/mL, 18.76±5.19 μg h/mL and 18.27±2.84 μg h/mL respectively. The Cmax and t1/2 of the sparfloxacin was 0.98±0.07 μg/mL, 14.91±1.30 h, 0.80±0.06 μg/mL, 15.75±2.37 h, 0.78±0.11 μg/mL, 16.01±1.98 and 0.81±0.04 μg/mL, 13.91±3.59 h respectively for the products A, B, C and D. The serum concentration of the sparfloxacin and other pharmacokinetic parameters obtained were statistically analyzed. The results of three-way analysis of variance of serum drug levels and pharmacokinetic parameters showed that there was no significant variation between the products, subjects and treatments at all the points of time with regard to the AUC0-α, Cmax and t1/2. The results of the study indicated that the products A, B, C and D are bioequivalent.